Save the Bees? Agrochemical Corporations and the Debate Over Neonicotinoids in Ontario. Issue 4 (2nd October 2019) - Ellis, Rebecca
ABSTRACT: There is widespread scientific agreement that bees are in global decline of health and/or population due to multiple factors, including loss of habitat, lack of wildflowers, and pesticides. Throughout Europe and North America, a debate has been raging about the effects of neonicotinoid pesticides on bees and other pollinators. This debate not only involves farmers, beekeepers, agrochemical corporations, and government officials but it also has captured the imagination of everyday people who are concerned with the plight of pollinators. This has led to a growing demand that neonicotinoid pesticides be banned or restricted. In 2015 Ontario, the largest province in Canada put in place a partial ban on this class of pesticides. In this paper, I will argue that agrochemical corporations intervened in multiple ways in the debate about neonicotinoid pesticides in Ontario, potentially weakening the legislation. Agrochemical corporations were heavily represented in the Ontario Bee Health Working Group and were consulted by government ministries throughout the process. Industry groups also worked with large farmers' organizations to shape the narrative about the impact of a neonicotinoid ban on farmers. While the agrochemical industry has considerable power and influence, there exists some hopeful possibilities for an agroecological counter-narrative that posits small-scale farmers as stewards of biodiversity.